Formation of a Chloride-conducting State in the Maltose ATP-binding Cassette (ABC) Transporter - Carlson, Michael L. (J Biol Chem, 2016)
ATP-binding cassette transporters use an alternating access mechanism to move substrates across cellular membranes. This mode of transport ensures the selective passage of molecules while preserving membrane impermeability. The crystal structures of MalFGK(2), inward- and outward-facing, show that the transporter is sealed against ions and small molecules. It has yet to be determined whether membrane impermeability is maintained when MalFGK(2) cycles between these two conformations. Through the use of a mutant that resides in intermediate conformations close to the transition state, we demonstrate that not only is chloride conductance occurring, but also to a degree large enough to compromise cell viability. Introduction of mutations in the periplasmic gate lead to the formation of a channel that is quasi-permanently open. MalFGK(2) must therefore stay away from these ion-conducting conformations to preserve the membrane barrier; otherwise, a few mutations that increase access to the ion-conducting states are enough to convert an ATP-binding cassette transporter into a channel.